Comparison of Deep Neuromuscular Block in Inhalation and Total Intravenous Anesthesia on Peritoneal Compliance and Surgical Conditions During Laparoscopic Cholecystectomy - Maryam Khoubnasabjafari; Mahmood Eidi; Hamzeh Hosseinzadeh (Pharmaceutical Sciences)
Background: Deep relaxation leads to improved surgical outcomes by providing more successful surgical conditions. In this study, the effect of rocuronium-induced deep relaxation on abdominal compliance and surgeon satisfaction in total intravenous anesthesia (TIVA) and inhalation anesthesia (IA) methods is investigated. The xiphopubic distance (XPD) is proposed as a simple measure of abdominal laxity. Methods: After premedication, 70 candidate patients for laparoscopic cholecystectomy (LC) are divided to TIVA and IA groups. In TIVA, propofol infusion at a dose of 60-100 μg/kg/min, and inIA isoflurane with MAC of 1-2 were used. After stabilization of intra-abdominal pressure (IAP), rocuronium is injected at a dose of 0.3 mg/kg to provide train of four (TOF) = 0 and post tetanic count (PTC) = 0. To check the degree of abdominal wall relaxation, the XPD is measured at 3 stages. The level of satisfaction of the surgeon is recorded. At the end of surgery, when TOFreceiving at least two responses, the anesthetic drugs are discontinued and antagonized. Results: The mean and frequency of most of the studied variables were the same in TIVA and IA groups and the observed differences were not statistically significant. The average change of heart rates in TIVA was significantly more than IA, and the arterial oxygen saturation in IA was more than TIVA. Deep relaxation and IAP of 15 mm Hg provided better surgical conditions, peritoneal compliance and surgeon’s satisfaction in both TIVA and IA methods and recovery was associated with the acceptable postoperative outcomes. The employed procedure does notrequire sugammadex as a reversing agent which reduces the cost of surgery. Conclusion: The deep relaxation induced by rocuronium in LC along with favorable IAP, good vision on the field and suitable surgical conditions in both IA and TIVA methods, and the difference in the findings related to the methods were not significant. Considering all aspects, the use of deep relaxation is recommended in LC with both anesthesia methods.